The Role of Physical Activity in the Prevention and Progression of Alzheimer’s Disease - Kaźmierczyk, Jakub; Popczyk, Michał; Jopek, Jakub; Marciszewska, Aleksandra; Tymchenko, Hanna; Piechowicz, Agnieszka; Popczyk, Natalia; Przybyłowska, Agnieszka; Buczkowska, Ewa; Świątecka, Martyna (Quality in Sport, 2026)
Introduction and aim Alzheimer’s disease (AD) poses a major public health challenge with limited pharmacological treatments, shifting focus to lifestyle interventions. This review analyzes the role of physical activity (PA) in preventing and modulating AD progression, focusing on cognitive function, brain structure, and molecular mechanisms. Materials and methods A literature search was conducted in the PubMed database, focusing primarily on Randomized Controlled Trials (RCTs) and observational cohort studies concerning PA interventions in Mild Cognitive Impairment (MCI) and AD. Summary: Evidence suggests PA significantly impacts clinical progression. In MCI, training may possibly delay conversion to dementia by 8-24 months, with neuroprotective effects sustaining post-intervention. Conversely, AD patients require continuous training to maintain benefits. Mechanisms involve "muscle-brain crosstalk" releasing neurotrophins (BDNF, IGF-1) and exerkines (irisin, cathepsin B, lactate), which promote neurogenesis and modulate neuroinflammation. Multimodal interventions (e.g., dance, Tai Chi) show superior cognitive outcomes compared to simple aerobic exercise. Efficacy is modulated by biological factors; APOE4 carriers and women may derive specific, distinct benefits from PA. Conclusions PA is a crucial non-pharmacological strategy for AD. High-intensity and multimodal training offer the greatest therapeutic potential. Since efficacy varies by genetic profile and sex, personalized recommendations are essential. Implementation at the preclinical stage is crucial for maximizing cognitive retention, yet introducing physical activity remains beneficial across all stages of AD.